Pengaruh Harga, Kualitas Produk dan Pelayanan Terhadap Keputusan Pembelian pada Kaki Empat Petshop Kediri - Uniza Nabella Haryanti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to determine the influence of price, product quality and service variables on purchasing decisions at Kaki Empat Petshop Kediri. This type of research is quantitative research which is used to test the relationship of a variable to other variables which emphasizes the analysis on numbers processed using statistical methods. This research data was obtained through questionnaires, interviews and literature studies. The population in this study were all consumers at Kaki Empat Petshop Kediri. The sample in this study was 244 respondents. The sampling technique uses accidental sampling. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. From the results of the research, it shows that the work experience variable (X1 The t test results of the price variable (X1) have a partially significant effect on purchasing decisions. Product quality (X2) has a partially significant effect on purchasing decisions. Service (X3) has a partially significant effect on purchasing decisions. The results of the F test can be concluded that price, product quality and service have a simultaneous and significant effect on purchasing decisions for Kaki Empat Petshop Kediri. Suggestions for Kaki Empat Petshop Kediri are to maintain things that can improve purchasing decisions.